2013
DOI: 10.1021/jp4026249
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures of Antimony Oxides

Abstract: This study details density functional theory calculations on all the polymorphs of the binary oxides of antimony (Sb 2 O 3 , Sb 2 O 4 , and Sb 2 O 5 ) to assess the electronic structures and differences in bonding between Sb III and Sb V ions with oxygen. The results show that lone-pair formation is via a similar mechanism to other main group elements which exhibit an oxidation state of two less than the group valence, through direct interaction of Sb 5s and O 2p states, with the antibonding interaction stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 92 publications
9
50
1
1
Order By: Relevance
“…The size of the fundamental and optical band gaps are therefore, dependent on the Sb s -Ch p anti-bonding interaction and the degree of mixing of states at the VBM, which effects the photo-physical properties of these and other similar lone pair materials. Sb 2 O 3 has a calculated fundamental and optical band gap greater than 3.1 eV making it a potential transparent conducting oxide with hole and electronic effective masses of 2.57 and 0.85, respectively [114]. The fundamental band gap of the antimony sulphide (1.29 eV), and selenide (0.75 eV) are indirect in nature, albeit underestimated by PBE, with their smallest direct gap being 1.36 eV and 0.78 eV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the fundamental and optical band gaps are therefore, dependent on the Sb s -Ch p anti-bonding interaction and the degree of mixing of states at the VBM, which effects the photo-physical properties of these and other similar lone pair materials. Sb 2 O 3 has a calculated fundamental and optical band gap greater than 3.1 eV making it a potential transparent conducting oxide with hole and electronic effective masses of 2.57 and 0.85, respectively [114]. The fundamental band gap of the antimony sulphide (1.29 eV), and selenide (0.75 eV) are indirect in nature, albeit underestimated by PBE, with their smallest direct gap being 1.36 eV and 0.78 eV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ÞÞ Antimony oxide is known to form three binary oxides, which have been widely used as dopants to enhance the material conductivity and elevate catalyst activity. [29][30][31] It has been demonstrated that antimony-doped catalysts are active and selective for several partial oxidation processes. [32] For example, doping SnO 2 oxide with Sb 3 + decreased the conductivity, whereas doping with SbV enhanced the n-type conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, crystals of AsV and SbV oxides pack quite differently due to the slightly larger size of the latter. This distinction in size and geometry,[7, 8] which can affect interactions with macromolecules,[9] may help rationalize that SbV has little obvious biological activity in human keratinocytes, indicating the rate of reduction to SbIII in them is too low to produce effects, despite the facile AsV reduction to AsIII in this cell type. [10]…”
Section: Introductionmentioning
confidence: 99%